PROJECT-BASED LEARNING OF ELT STUDENTS ON ESSAY WRITING - Maya Sari, Dina Merris; Prasetyo, Yudy; Riza, Muhammad Dicky (Premise: Journal of English Education and Applied Linguistics, 2023)
Essay writing has always been an important skill for students. However, this skill could be more comfortable for them. Therefore, an effective technique is needed to help students to cope with the problem. Project-based learning (PjBL)is one of the learning models which can make learners interested and motivated in writing. The study employs expose-facto with mixed data types. This research investigated 23 English students activities, results, and their responses in essay writing using a PjBL model. We employed three instruments; observation, questionnaire, and test. Qualitative descriptive techniques analyzed the data. The results showed that (1) the implementation of the project-based learning model was classified as good and successful. It can be seen from the student's learning outcomes and the successful implementation of the steps that have been determined. (2) The students responses to the project-based learning model have been classified as positive since the students explained effective ways of learning essay writing. The students learning outcomes show better achievements in learning essay writing. Thus, learning essay writing can be concluded. It implies that implementing the PjBL model in ELT students yields good vibes in students learning activities.